2005
DOI: 10.1007/s00402-005-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Micromotion in cemented rotating platform total knee arthroplasty: cemented tibial stem versus hybrid fixation

Abstract: In conclusion, the stem of mobile bearing tibial components should be cemented to provide increased micromotion and earlier loosening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…If the cement mantle was 3 mm thick or the stem was cemented, the micromotion decreased significantly. Also cadaver studies by Jazrawi et al [10] and Luring et al [12] revealed significantly increased micromotion when only cementing the tibial baseplate. Contrary to these in vitro studies, Peters et al did not find less micromotions when cementing the stem in cadaver knees [13].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…If the cement mantle was 3 mm thick or the stem was cemented, the micromotion decreased significantly. Also cadaver studies by Jazrawi et al [10] and Luring et al [12] revealed significantly increased micromotion when only cementing the tibial baseplate. Contrary to these in vitro studies, Peters et al did not find less micromotions when cementing the stem in cadaver knees [13].…”
Section: Discussionmentioning
confidence: 95%
“…However, Hyldahl et al showed in a radiostereometry (RSA) study that fixation was better at the two-year followup if the tibial stem was cemented [7,8]. In vitro studies have shown less micromotion when complete cementing is used [2,10,12], but Peters et al did not confirm this finding in a cadaver study [13].…”
Section: Introductionmentioning
confidence: 99%
“…Highly localised peri-prosthetic plasticity has also been observed experimentally during vertebral fusion device subsidence [16]. Correct prediction of this stress distribution at the bone implant-interface will have implications for device design and in particular for peri-prosthetic bone remodelling and initial implant stability of the tibial component, which have been investigated in previous biomechanical studies [7,[17][18][19][20][21]. To our knowledge, the current study is the first to implement the CFI plasticity formulation for the trabecular material in the investigation of press-fit stem implantation in total arthroplasty.…”
Section: Discussionmentioning
confidence: 98%
“…There have been a few reports of tray micromotion and subsidence under cyclic loading in human cadaver tibiae. Factors that have been shown to significantly affect tray subsidence include the type of loading, the density of cancellous bone, the presence of a cement interface, the length of the tibial stem, and the *Address correspondence to this author at the 11025 North Torrey Pines Road, Suite 200, La Jolla, CA 92037, USA; Tel: 858-332-0166; Fax: 858-332-0669; Email: ddlima@scripps.edu presence of screw fixation [9][10][11][12][13]. However, the effect of tibial tray alignment has not been fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…Surrogate bone models have been used to simulate the mechanical behavior of human bone [10]. A cementless tray when tested under cyclic loading (1000 N axial compression and 250 N horizontal shear) subsided 400 to 800 µm in a polyurethane surrogate bone with orthotropic material properties [14].…”
Section: Introductionmentioning
confidence: 99%